STANDARISASI EKSTRAK ETIL ASETAT KAYU SANREGO (LUNASIA AMARA BLANCO) - Anam, Syariful; Yusran, Muhammad; Trisakti, Alfred; Ibrahim, Nurlina; Khumaidi, Ahmad; Ramdanil, Ramdanil; Zubair, Muhammad Sulaiman (Natural Science: Journal of Science and Technology, 2013)
Lunasia amara Blanco is a popular medicinal plant which is known as aphrodisiac in South Sulawesi Province. Biological activity as antibacterial, anticancer dan antituberculosis were also scientifically reported. This study is to ascertain the safety and quality of the plant extract by standardization procedures mentioned in literature, including specific and non-specific parameters. The result showed that ethyl acetate wood extract of L. amara Blanco, which is brown viscous extract, astringent to the taste and characteristic odor, contain water-soluble extractive matters of 23,95 ± 2,192 %, ethanol-soluble extractive matters of 67,05 ± 3,61 %, water content of 5,33 ± 0,407 %,  total ash content of 0,65 ± 0,199 %, acid-insoluble ash content of 0,58 ±0,225 %, density of 0,7734 ± 0,0016 (5%) and 0,7957 ± 0,0021 (10%), total contaminant number of bacteria and fungus of each < 1 x 104 colony/g, and Pb concentration of 10,59 ± 0,239 mg/kg. Ethyl acetate wood extract of L. amara Blanco has been qualified as standardized extract. Therefore, this study can be a reference for identification and control quality of the extract as a herb-medicine material